ANAEROBIC DIGESTION AS CENTRE OF DAIRY LIVESTOCK AND AGRICULTURE INTEGRATION: BASIS FOR MEDIUM-SCALE CDM PROJECTS DEVELOPMENT - Fiorelli, F. A. S.; Diaz, G. O. (Revista de Engenharia Térmica, 2007)
Dairy producers should improve their activity with modern production techniques/technologies to meet the requirements of a stricter consumer market. In this sense, crop and livestock systems integration represents an interesting alternative for using the dairy farm available resources. This paper analyses the use of anaerobic digestion as basis for supplying energy, fertilizers and feed needs of a farming unit, by means of digestion products usage: biogas, which can be used in energy conversion systems to provide the required energy for processing/conservation equipment for milk and other farming products; and effluent, that can be used as a replacement for chemical fertilizers and for aquatic plants/fish feeding. Fossil fuels replacement by biogas can be classified as a Clean Development Mechanism (CDM) project, and economic resources obtained by carbon credits commercialisation may support the required production modernisation. The paper analyses the anaerobic digestion process, evaluating biogas in medium-scale dairy farms, as well as the quantification of carbon credits generated by introducing proper manure and culture remains management.